ISLAM, KESEHATAN DAN LINGKUNGAN HIDUP: Studi Tentang Jamu Madura - Sri Handayani (Institut Agama Islam Negeri Madura)
AbstracIslamic teaching, to maintain quality of healthy life, has inspired Madurese. This island has treasure of culture that harmonizes Islamic credo. This article studies people’s notion on Madurese herbal ingredients, the existence of Madurese herbs in dealing with environment conservation, socio-cultural value, and today’s people perception toward Madurese herbs. The result of study shows that Madurese herbs has been the work of Madurese ancestors and piece of traditional treasury to keep a healthy life. Presently, it is assumed that Madurese herbs hold up the harmony of husband and wife intimate relationship. This is undeniable fact but Madurese herbs also enclose the other restorative power instead. The cultivation of Madurese herbal ingredients will give a good impact to the effort of environment conservation. This is also expected to preserve the drinking help tradition as a medium to have a healthy life. To conserve environment means to obey the Islamic teachingKata-kata Kuncijamu Madura, lingkungan hidup, sosial-budaya